PENERAPAN SISTEM INFORMASI MANAJEMEN DALAM MANAJEMEN BERBASIS SEKOLAH (STUDI KASUS PADA SISTEM INFORMASI AKADEMIK STIT AL-IHSAN BALEENDAH) - Noviyanti; Amalia, Rosemila; Mustika, Sri; Salinan; Warta, Waska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of information and communication technology has significantly impacted the education sector, particularly in improving the effectiveness, efficiency, and accountability of school management. This study aims to analyze the implementation of a Management Information System (MIS) to support School-Based Management (SBM) at STIT Al-Ihsan Baleendah. Using a descriptive qualitative case study approach, the research explores planning, organizing, implementation, and evaluation of MIS in the institution. Data were collected through interviews, observations, and document analysis, then analyzed interactively. The findings show that MIS has accelerated academic administrative services, improved data accuracy, and facilitated data-driven decision-making. However, challenges remain, including limited infrastructure, insufficient digital literacy among staff, and lack of formal documentation. Regular evaluation and continuous improvement efforts are crucial for sustainable system performance. This study contributes to both theory and practice by providing insights into the integration of MIS and SBM in Islamic higher education contexts. Keywords: Management Information System, School-Based Management, Higher Education, Academic Administration, Digital Literacy;